2022
DOI: 10.3390/cancers14040979
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Tumor Markers in Central Nervous System Germ Cell Tumors Revisited with Histopathology-Proven Cases in a Large International Cohort

Abstract: The central nervous system germ cell tumor (CNS GCT) is a rare and incompletely understood disease. A major outstanding question in the 2015 consensus document for CNS GCT management was the utility and interpretation of the tumor markers human chorionic gonadotropin (HCG) and alpha fetoprotein (AFP) in the diagnosis of malignant non-germinomatous GCTs (hereafter NGGCTs) prior to treatment. In the current study, we assembled two geographically and ethnically different clinical cohorts from the Mayo Clinic (198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The current study extends our preceding work regarding the evolving understanding of tumor markers in CNS GCTs [ 15 ]. Our previous study demonstrated that elevation of tumor marker alone cannot exclude the possibility of germinoma or teratoma within the true histopathologic profile of a given GCT.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The current study extends our preceding work regarding the evolving understanding of tumor markers in CNS GCTs [ 15 ]. Our previous study demonstrated that elevation of tumor marker alone cannot exclude the possibility of germinoma or teratoma within the true histopathologic profile of a given GCT.…”
Section: Discussionsupporting
confidence: 76%
“…The combined study cohort correspondingly included 161 cases: 40 from Mayo Clinic, 121 from iGCT consortium. One case was omitted from the preceding study [ 15 ], as the timing of tumor marker measurement and surgical resection was not strictly identical.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, mild elevations of serum β-HCG or AFP could be observed in pure germinomas. 5,22,23 Although serum and CSF AFP accounted for a higher percentage of agreement than β-HCG, the overall consistency between serum and CSF AFP and β-HCG levels was desirable with a moderate level of agreement. This could imply that assessing either serum or CSF is sufficient for diagnostic evaluation to lower the unnecessary lumbar puncture procedures among patients with ICGCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Although many investigators have studied diagnostic criteria for tumor markers, no international consensus has been reached regarding clinical diagnostic criteria for biochemical marker levels. 21 Furthermore, no reports have clarified the clinical significance of CA19-9 in CNS GCTs.…”
Section: Discussionmentioning
confidence: 99%